Application of Sinc-Galerkin Method for Solving Space-Fractional Boundary Value Problems - Alkan, Sertan; Secer, Aydin (HINDAWI LTD, 2015)
We employ the sinc-Galerkin method to obtain approximate solutions of space-fractional order partial differential equations (FPDEs) with variable coefficients. The fractional derivatives are used in the Caputo sense. The method is applied to three different problems and the obtained solutions are compared with the exact solutions of the problems. These comparisons demonstrate that the sinc-Galerkin method is a very efficient tool in solving space-fractional partial differential equations.
Keywords: DIFFERENTIAL TRANSFORM METHOD; HOMOTOPY PERTURBATION METHOD; NUMERICAL-SOLUTIONS; EQUATIONS; ORDER; Engineering; Mathematics